Safety of mRNA BNT162b2 COVID-19 (Pfizer-BioNtech) vaccine in children aged 5–11 years: Results from an active pharmacovigilance study in central Italy. Issue 6 (30th November 2022) - Ripabelli, Giancarlo; Sammarco, Michela Lucia; D'Amico, Antonio; De Dona, Roberta; Iafigliola, Mariagrazia; Parente, Albino; Samprati, Nicandro; Santagata, Arturo; Adesso, Carmen; Natale, Anna; Di Palma, Michela Anna; Cannizzaro, Fabio; et al.
ABSTRACT: This survey investigated on adverse events after vaccination with mRNA BNT162b2 (Comirnaty, Pfizer-BioNTech) vaccine in children aged 5–11 years in central Italy through active surveillance reporting. During December 2021–January 2022, parents of children who undergone vaccination were interviewed using a structured questionnaire. 197 out of 208 contacted parents participated (94.7% response rate), of whom 166 (84.3%) had one child. Of the 229 children, the mean age was 8.9 years, 50.7% were female. 193 (84.3%) had at least one adverse event after the first dose (mean age 9.1 years; 54.4% female), and 146 (73.4%) of 199 after the second (mean age 8.9 years; 54.8% female), which was not administered to 30 children due to previous COVID-19 history. Local symptoms after the first and second dose occurred in 183 (94.8%) and 141 (96.6%) recipients (p = .435), respectively, while systemic reactions in 62 (32.1%) and 34 (23.3%) ( p  = .074). Mild events were reported by 81.7% and 69.8% children after the first and second dose, followed by moderate (3.9% and 10.6%) and severe (1.3% and 0.5%). After each dose, injection site reactions (79.5% and 68.8%) were the most frequent, followed by headache (13.1%) and lymphadenopathy (8.5%) after the first and second dose, respectively. The adverse events were reported to pediatricians only for 5.7% and 3.9% of children and treated for 17.6% and 15.8%. This is the first report about safety profile through active surveillance of mRNA BNT162b2 among children in Italy, revealing temporary and mild-to-moderate symptoms with no serious events after each vaccine dose.